2011
DOI: 10.1007/s11427-010-4132-z
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism for the formation of annual growth lines in bivalve shells

Abstract: We report a unique shell margin that differed from the usual shell structure of Pinctada fucata. We observed empty organic envelopes in the prismatic layer and the formation of the nacreous layer in the shell margin. All the characteristics of the growing margin indicated that the shell was growing rapidly. To explain this anomaly, we propose the concept of "jumping development". During jumping development, the center of growth in the bivalve shell jumps forward over a short time interval when the position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Figure I depicts the nacreous layer of B. costula where crystal fibers are piled up to follow a typical brick-and-mortar wall model . In addition to the above-mentioned conventional morphological structures of snail shells, a variety of exclusive crystalline arrangements of indecisive mineralogical assembly-created homogeneous structures are spread throughout the different shell layers in a diverse manner.…”
Section: Resultsmentioning
confidence: 99%
“…Figure I depicts the nacreous layer of B. costula where crystal fibers are piled up to follow a typical brick-and-mortar wall model . In addition to the above-mentioned conventional morphological structures of snail shells, a variety of exclusive crystalline arrangements of indecisive mineralogical assembly-created homogeneous structures are spread throughout the different shell layers in a diverse manner.…”
Section: Resultsmentioning
confidence: 99%
“…; Liu et al . ,b;) were not found in H. cumingii (Figs and A). Growth of crystals without the presence of mature interprismatic organic membranes was observed on the organic layer in the shell margin (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Checa et al (2005), however, hypothesized that the organic frameworks of the prismatic layer may form in the absence of mineral infilling. Liu et al (2011b) recently observed empty organic frameworks in the prismatic layer in the shell margin of the bivalve Pinctada fucata. In another study, phosphate buffer-soluble proteins secreted by the margin of the mantles (MSPs) were observed to reconstruct the stages in the growth of the prismatic layer of the decalcified organic frameworks, and a model of the prismatic layer formation in this specimens was shown (Liu et al 2011a).…”
Section: Introductionmentioning
confidence: 97%